«CROSS-TRAILS» OF IVAN FRANKO AND «CRIME AND PUNISHMENT» OF FYODOR DOSTOEVSKY IN THE LIGHT OF THE JURISPRUDENCE OF THE LATE XIXth – EARLY XXth CENTURIES - Shyshko, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In this article it was made the comparison of the story of Ivan Franko «The cross-roads» with the novel of Fyodor Dostoevsky «The crime and the punishment» and analyzed the problems and collisions of these stories with the point of the civil and the criminal law.